A better understanding of testicular and/or epididymal tuberculosis based on clinical, ultrasonic, computed tomography, and magnetic resonance imaging features at a high-volume institute in the modern era - Li, Shuang (Quant Imaging Med Surg, 2021)
BACKGROUND: There is a concerning underdiagnosis of testicular and/or epididymal tuberculosis (TB). A lack of clinician awareness has led to many patients undergoing unnecessary surgeries. The purpose of this series was to enhance understanding of testicular and/or epididymal TB based on clinical, ultrasonic, computed tomography (CT), and magnetic resonance imaging (MRI) features from the past decade. METHODS: We retrospectively investigated the medical records of 69 patients diagnosed with testicular and/or epididymal TB from 2008 to 2019. All participants were diagnosed by confirmation of Mycobacterium tuberculosis in the histopathology of resected samples. Baseline characteristics, ultrasonic, CT, and MRI features were collected for analysis. RESULTS: A total of 69 patients with a median age of 43.5 years were included in the study. Testicular-epididymis TB, epididymal TB, and testicular TB were confirmed in 31 (44.9%), 26 (37.7%), and 12 (17.4%) patients, respectively. In sonography, testicular TB and epididymal TB imaging features are significantly different (P<0.001). Diffusely enlarged lesion heterogeneously (33/58, 56.9%) is most common in the epididymis, and miliary type (18/39, 46.2%) is most common in the testis. On enhanced CT, annular or multilocular enhancement pattern (19/21, 90.5%) was the characteristic manifestation of our patients. CONCLUSIONS: Laboratory findings [especially T lymphocyte spot test for tuberculosis infection (T-SPOT.TB)], accompanied by scrotal sonography and enhanced CT examinations, can help distinguish testicular and/or epididymal TB from other etiologies.